Color of ‘bengal’ litchis after exposure to UV-C light and refrigerated storage - Furlaneto, Karina A. [UNESP]; Ramos, Juliana A. [UNESP]; Daiuto, EÉrica R. [UNESP]; Fujita, EÉrika [UNESP]; De Mendonça, Veridiana Z. [UNESP]; Vieites, Rogério L. [UNESP]; De Carvalho, Lidia R. [UNESP]; Smith, Robert E. (Bentham Science Publishers, 2014)
The effect of UV-C radiation on the preservation of refrigerated ‘Bengal’ litches (Litchi chinensis Sonn.) was determined. Fruits were submitted to UV-C light for 10, 20 and 30 mins, while being stored at 5±0.5 oC and 90±5% relative humidity for 15 days. The concentration of total phenolics was highest in the fruits that were exposed to UV-C for 10 and 20 mins. The activities of the enzymes polyphenol oxidase (PPO) and polyphenol peroxidase (PPP) were only affected by the days of storage, with minimum activity on day 6 for PPO and day 15 for PPP. The visual appearance also changed during storage, with the fruits being brighter after 20 and 30 mins of exposure to UVC light. Moreover, the fruits had a higher color index due to their red color after being exposed to UV-C light for 30 mins.
Keywords: (Litchi chinensis Sonn); Litchis; Phenol; Polyphenol oxidase; Polyphenol peroxidase; Postharvest treatment